Supercritical fluid CO2 extraction of essential oil from Marchantia convoluta: global yields and extract chemical composition - Xiao, Jian Bo; Chen, Jing Wen; Xu, Ming (Electronic Journal of Biotechnology, 2007)
The essential oil of Marchantia convoluta was obtained by supercritical (carbon dioxide) extraction using methanol as a modifier. Global yields were determined according to the orthogonal design. The effects of different parameters, such as pressure, temperature, modifier volume and extraction time, on the supercritical fluid extraction (SFE) of essential oil from M. convoluta were investigated. Maximum global yields were obtained using the following conditions: extraction temperature, 35ºC; dynamic time, 35 min; pressure, 15 Mpa and modifier volume, 40 mL. The essential oil extract was analyzed by capillary gas chromatography with mass spectrometric detector (GC-MS). The compounds were identified according to their retention indices and mass spectra (EI, 70 eV). The results from GC-MS and literature were compared.